2017
DOI: 10.18805/ijar.b-3300
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic studies on Nellore and Deccani sheep using microsatellite markers

Abstract: The study was undertaken to understand the genetic architecture of Deccani and Nellore sheep breeds and to assess the genetic distance between the breeds. Allele diversity, genetic variability and population structure in the two breeds were estimated using 30 microsatellite markers. A total of 100 sheep, 50 each from Deccani and Nellore breeds were genotyped. The total number of alleles observed was 254 and 260 in Deccani and Nellore, respectively. The mean expected heterozygosity among the breeds ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Six loci each in Assam and Meghalaya sheep and eight loci in Arunachal Pradesh sheep were found to be monomorphic for which no subsequent analysis was done. Similar reports of 242 alleles scored in different sheep breed was reported by Amareswari et al (2018) in Deccani (254 alleles) and Nellore sheep breed (260 alleles) and Molabanti et al (2019) in Macherla Brown sheep breed (275 alleles). However, lower total alleles scored by Ravimurugan (2015) in Madras Red sheep breed (175 alleles) and Martínez et al (2021) in Mexican Pelibuey sheep population (99 alleles); and a higher total allele was scored in Deccan sheep (407 alleles) by Yadav et al (2017).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Six loci each in Assam and Meghalaya sheep and eight loci in Arunachal Pradesh sheep were found to be monomorphic for which no subsequent analysis was done. Similar reports of 242 alleles scored in different sheep breed was reported by Amareswari et al (2018) in Deccani (254 alleles) and Nellore sheep breed (260 alleles) and Molabanti et al (2019) in Macherla Brown sheep breed (275 alleles). However, lower total alleles scored by Ravimurugan (2015) in Madras Red sheep breed (175 alleles) and Martínez et al (2021) in Mexican Pelibuey sheep population (99 alleles); and a higher total allele was scored in Deccan sheep (407 alleles) by Yadav et al (2017).…”
Section: Resultssupporting
confidence: 84%
“…A relatively similar finding for number of alleles was reported by Arora et al(2008) and Pramod et al (2009) in Jalauni and Vembur sheep breeds which ranged from two to nine. However, a higher range was reported by Amareswari et al (2018) The observed and effective numbers of alleles are also an index used to reveal the genetic diversity of the populations. The mean observed numbers of alleles (N a ) were found to be 3.160, 3.360 and 3.160 in Assam, Meghalaya and Arunachal Pradesh sheep respectively.…”
Section: Resultsmentioning
confidence: 95%
“…By contrast, a remarkable difference between H o and H e was observed for LPK chicken population, where H o was higher than H e , and there was no subpopulation within LPK chicken population examined (negative F value). This higher heterozygosity than expected may reflect that genetic contamination, such as outbreeding with individuals from populations with different origins or ecotypes, occurred during the process of breeding in the past [ 50 , 51 ]. In the Lamphun region, a suitable environment for both LPK chickens and red junglefowl is provided by the forest.…”
Section: Discussionmentioning
confidence: 99%
“…Further research can be carried out by comparing samples from other regions in Indonesia and from neighboring countries [ 40 ]. Apart from studying part of mtDNA, more detailed studies can also be carried out such as microsatellite [ 41 , 42 ], complete mitochondrial genome [ 27 , 43 ], whole-genome DNA [ 44 , 45 ], and the other studies using the next-generation sequencing [ 46 ] and/or the other methods.…”
Section: Discussionmentioning
confidence: 99%